ENERGY PERFORMANCE OF DISTRIBUTED GENERATION EXPANSION IN PUBLIC HIGHER EDUCATION INSTITUTIONS: A CASE STUDY OF THE FEDERAL INSTITUTE OF EDUCATION, SCIENCE, AND TECHNOLOGY OF PIAUÍ, BRAZIL - Silva, Osvaldo Augusto Vasconcelos de Oliveira Lopes da; Morais, Fabrício Higo Monturil de; Ribeiro, Fernando Rodrigues; Leite, Cristiana de Sousa (Revista Econômica do Nordeste, 2026)
Distributed generation (DG) has experienced significant expansion in Brazilian public higher education institutions (HEIs) since 2020. Thus, this article aims to evaluate the energy performance of facilities involved in this scenario. Initially, the integration of DG into the public sector was assessed. Considering the Federal Institute of Education, Science, and Technology of Piauí (IFPI) as a case study, the expansion of DG is characterized through technical, economic, and environmental indicators. Although an increase is observed in DG capacity in this sector, there is a low representation of such systems in the DG energy mix. The expansion proved to be feasible, resulting in improved technical and economic indicators of the systems, increased efficiency and average power ratings of inverters and photovoltaic (PV) modules, as well as the simplification of arrangements. However, only half of the initially contracted systems were commissioned. The installation did not comply with technical criteria in the selection of location and equipment as well, thus denoting the need for improving such issues to ensure higher efficiency. Finally, it was found that the expansion continues to the date, whereas the used methodology was found to be applicable to other institutions, providing guidance for the procurement of new systems.